CULTURAL INFLUENCES ON STUDENTS’ PERCEPTIONS OF WRITTEN FEEDBACK IN L2 WRITING - Fithriani, Rahmah (Journal of Foreign Language Teaching and Learning, 2018)
One of significant topics to discuss in studies about feedback in L2 writing is the influence of students? culturally constructed view of the feedback process. Research has shown that the cultures of hierarchical relationship and face-saving strategy have significant influence on students? perceptions of feedback process in L2 writing, particularly in Asian societies. Aiming to investigate whether these findings resonate in Indonesian EFL context, this study collected data through writing drafts, reflective journals, questionnaires and interviews with seven students who took an after-class writing course. Findings suggested that students valued teacher feedback more than peer feedback, however they were not concerned about practicing face-saving strategies to maintain group harmony and cohesion.